A comparative study between the oral health status of grade 6 pupils of public schools, with and without a school dental health program SY 2002-2003 - Molato, Risha R.; Serraon, Antolin (Adviser).
The importance of the oral health status of children is significantly relevant to the future of a nourishing lifestyle. With the help of a school dental health program, children are able to mold their beliefs, interests, motives, values, perceptions towards quality health as foundation of an upright education. This study aimed to compare the oral health status of grade 6 pupils in public schools, with and without school dental health programs. The study was conducted in two pre-selected urban public schools: Pinyahan Elementary School and Tomas Morato Elementary School. A total of 120 subjects undergone oral examination utilizing the Mean DM FT Index and Mean Percentage Hygiene Index. Based on the results, there is a significant difference between the Mean DMFT yet no significant difference between the Mean Percentage Hygiene Index of grade 6 pupils in public schools, with and without a school dental health program.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health; Dental Health Program